Aggressive conflict in Southern Thailand: roots of hostility and aggression - Che Mohd Aziz Yaacob, (Penerbit UKM, 2013)
Violent conflict occurred in Southern Thailand in the year 2004. Since then, there has continued to be a spiral of violence without any sign of abatement. Events such as shooting, ambushing, bombing, arson, kidnapping and threatening letters constantly threaten the local inhabitants and exacerbate tensions between the Patani United Liberation Movement and the Thai government. Despite a pro-active effort by the Thai government and civil interest groups in searching for solutions, there has been no sign of a resolution. Therefore, this paper aims to contribute to this dialogue by exploring the roots of the conflict from the perspective of the ordinary people involved; especially those supporters of the Patani United Liberation Movement. Discussion will focus on the role of violence during the conflict and will also consider suggestions as to a resolution based on non-violent methods using an approach known as conflict transformation within peace and conflict psychology.